Structure having three-dimensional curved surface

CN122953589APending Publication Date: 2026-10-20ASAHI KASEI KOGYO KABUSHIKI KAISHA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202580022038.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-27
Filing Date
2025-03-27
Publication Date
2026-10-20

AI Technical Summary

Benefits of technology

[0036]根据本发明的一个方式,能够提供一种具有三维曲面的结构体,其能够在任意的方向上控制电磁波。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

A structure is provided, which is a structure with a three-dimensional curved surface, having sequentially a metal layer, a dielectric, and a metal pattern region on the surface of the dielectric, wherein the diameter of the smallest enclosing sphere of the metaatoms constituting the metal pattern region is 3 μm or more and 100 mm or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to structures with three-dimensional curved surfaces. Background Technology

[0002] In recent years, the development of remote operation technology for electronic devices and the popularization of VR have created a demand for higher-speed and higher-capacity communication. To achieve such communication, higher-frequency electromagnetic waves are required. Generally, compared to low-frequency electromagnetic waves, high-frequency electromagnetic waves are less prone to diffraction, and are shielded by obstacles. Therefore, there is a need for electromagnetic wave control elements that can allow electromagnetic waves to bypass obstacles and reach their target location. For example, research is underway on using metamaterials (more specifically, artificial materials with periodic structures whose dimensions are smaller than the wavelength of the electromagnetic wave, thus exhibiting behaviors not found in naturally occurring matter) to control the direction of electromagnetic waves.

[0003] For example, Non-Patent Document 1 discloses a planar metamaterial characterized by forming a plate-shaped dielectric with a thickness of about 50 nm on a gold foil, and fabricating a gold pattern on the plate-shaped dielectric using photolithography to reflect electromagnetic waves of 333 THz to 400 THz.

[0004] For example, Non-Patent Document 2 discloses a planar metamaterial characterized by using photolithography to create copper patterns on both sides of a plate-shaped dielectric with a thickness of about 0.787 mm to concentrate electromagnetic waves of 35 GHz to 40 GHz.

[0005] Existing technical documents

[0006] Patent documents

[0007] Non-patent literature 1: Nano Lett., 2012, 12, 6223

[0008] Non-patent literature 2: Sci. Rep., 2021, 11, 12671 Summary of the Invention

[0009] The problem that the invention aims to solve

[0010] However, the planar metamaterials described in Non-Patent Documents 1 and 2 have the problem that they cannot be arranged in the form of a shell along a three-dimensional curved surface. Furthermore, planar metamaterials suffer from the following problem: the incident angle of an electromagnetic wave irradiating the planar metamaterial from a specific direction is approximately constant at any point on the metamaterial. If the incident angle is constant, the control direction of the electromagnetic wave is limited. Non-Patent Documents 1 and 2 do not adequately address the aforementioned problems caused by the planar shape of the structure.

[0011] The purpose of this invention is to solve the above-mentioned problems and provide a structure with a three-dimensional curved surface that functions as a metamaterial and can be controlled by electromagnetic waves.

[0012] It should be noted that, in this disclosure, the function of the structure as a metamaterial refers to its ability to control the direction of electromagnetic waves in directions that cannot be achieved through ordinary mirror reflection and refraction.

[0013] Methods for solving problems

[0014] This disclosure includes the following items.

[0015] [Item 1]

[0016] A structure, which is a structure with a three-dimensional curved surface. It sequentially comprises a metal layer, a dielectric, and a metal pattern area on the surface of the dielectric. The diameter of the smallest enclosing sphere of the metaatoms constituting the above-mentioned metal pattern region is between 3 μm and 100 mm.

[0017] [Item 2]

[0018] According to the structure described in item 1, a metal compound layer is further present inside the aforementioned metaatoms.

[0019] [Item 3]

[0020] According to the structure described in item 1 or 2, the metal constituting the aforementioned metaatoms comprises copper.

[0021] [Item 4]

[0022] According to the structure described in item 2, the metal constituting the superatoms and the metal compound layer comprises copper.

[0023] [Item 5]

[0024] The structure according to any one of items 1 to 4, wherein a resin layer is further provided on the outer side of the aforementioned metal pattern area.

[0025] [Item 6]

[0026] The structure according to any one of items 1 to 5, wherein the carbon / metal elemental concentration ratio of the aforementioned metaatom is 1.0 or more and 6.0 or less.

[0027] [Item 7]

[0028] The structure according to any one of items 1 to 6, wherein the water absorption rate of the dielectric is 0.2 or less.

[0029] [Item 8]

[0030] According to any one of items 1 to 7, the area of ​​the aforementioned metal pattern region is 0.09 mm². 2 Above 20m 2 the following.

[0031] [Item 9]

[0032] The structure according to any one of items 1 to 8, wherein the operating frequency is 0.3 GHz or more and 10 THz or less.

[0033] [Item 10]

[0034] An electromagnetic wave transceiver system comprising the structure described in any one of claims 1 to 9 and an electromagnetic wave oscillation antenna.

[0035] Invention Effects

[0036] According to one aspect of the present invention, it is possible to provide a structure with a three-dimensional curved surface that can control electromagnetic waves in any direction. Attached Figure Description

[0037] Figure 1 This is a diagram illustrating the structure fabricated in the embodiment.

[0038] Figure 2 This is a diagram illustrating the cross-sectional structure of the structure fabricated in the embodiment.

[0039] Figure 3 This is a diagram showing the result of the reflection direction when electromagnetic waves are incident on the structure fabricated in the embodiment.

[0040] Figure 4 This is a top view of the structure fabricated in Example 2.

[0041] Figure 5 This is a cross-sectional view of the structure fabricated in the embodiment.

[0042] Figure 6 This is a graph showing the calculated angular distribution of the reflected wave intensity in the xz plane under a frequency of 300 GHz in the structure of Embodiment 2.

[0043] Figure 7 This is a graph showing the calculated angular distribution of the reflected wave intensity in the yz plane under a frequency of 300 GHz in the structure of Embodiment 2.

[0044] Figure 8 This diagram illustrates the azimuth and polar angles of the reflection direction in the xyz coordinate system.

[0045] Figure 9 This is a diagram of the device configuration used when performing functional verification tests as a metamaterial on a structure fabricated in the embodiments.

[0046] Figure 10 The evaluation results are obtained when the structure of Example 2 is used for functional verification testing as a metamaterial. The graph shows the angular distribution of the reflected wave intensity under a frequency of 300 GHz.

[0047] Figure 11 This is a top view of the structure fabricated in Example 3.

[0048] Figure 12 This is a graph showing the calculated angular distribution of the reflected wave intensity in the xz plane under a frequency of 300 GHz in the structure of Embodiment 3.

[0049] Figure 13 This is a graph showing the calculated angular distribution of the reflected wave intensity in the yz plane under a frequency of 300 GHz in the structure of Embodiment 3.

[0050] Figure 14 The evaluation results of the structure of Example 3 as a metamaterial functional verification test are shown in the graph, which shows the angular distribution of the reflected wave intensity under the 300 GHz frequency condition.

[0051] Figure 15 This is a top view of the structure fabricated in Example 4.

[0052] Figure 16 This is a graph showing the calculated angular distribution of the reflected wave intensity in the xz plane under a frequency of 300 GHz in the structure of Embodiment 4.

[0053] Figure 17 This is a graph showing the calculated results of the angular distribution of the reflected wave intensity in the yz plane under a frequency of 300 GHz in the structure of Embodiment 4.

[0054] Figure 18 The evaluation results of the structure of Example 4 as a metamaterial functional verification test are shown in the graph, which shows the angular distribution of the reflected wave intensity under a frequency of 300 GHz.

[0055] Figure 19 This is a top view of the structure fabricated in Example 5.

[0056] Figure 20 This is a graph showing the calculated angular distribution of the reflected wave intensity in the xz plane under a frequency of 300 GHz in the structure of Embodiment 5.

[0057] Figure 21 This is a graph showing the calculated angular distribution of the reflected wave intensity in the yz plane under a frequency of 300 GHz in the structure of Embodiment 5.

[0058] Figure 22 The evaluation results of the structure of Example 5 as a metamaterial functional verification test are shown in the graph, which shows the angular distribution of the reflected wave intensity under a frequency of 300 GHz.

[0059] Figure 23 This is a top view of the structure fabricated in Example 6.

[0060] Figure 24 This is a graph showing the calculated results of the angular distribution of the reflected wave intensity in the xz plane under a frequency of 300 GHz in the structure of Embodiment 6.

[0061] Figure 25 This is a graph showing the calculated results of the angular distribution of the reflected wave intensity in the yz plane under a frequency of 300 GHz in the structure of Embodiment 6.

[0062] Figure 26 This is a graph showing the calculated angular distribution of the reflected wave intensity in the xz plane under a frequency of 300 GHz in the structure of Embodiment 7.

[0063] Figure 27 This is a graph showing the calculated angular distribution of the reflected wave intensity in the yz plane under a frequency of 300 GHz in the structure of Embodiment 7.

[0064] Figure 28 This is a graph showing the calculated angular distribution of the reflected wave intensity in the xz plane under a frequency of 300 GHz in the structure of Embodiment 8.

[0065] Figure 29 This is a graph showing the calculated results of the angular distribution of the reflected wave intensity in the yz plane under a frequency of 300 GHz in the structure of Embodiment 8.

[0066] Figure 30 This is a graph showing the calculated angular distribution of the reflected wave intensity in the xz plane under a frequency of 300 GHz in the structure of Embodiment 9.

[0067] Figure 31 This is a graph showing the calculated results of the angular distribution of the reflected wave intensity in the yz plane under a frequency of 300 GHz in the structure of Embodiment 9.

[0068] Figure 32 This is a top view of the structure fabricated in Example 10.

[0069] Figure 33 This is a graph showing the calculated results of the angular distribution of the reflected wave intensity in the xz plane under a frequency of 1.05 THz in the structure of Embodiment 10.

[0070] Figure 34 This is a graph showing the calculated results of the angular distribution of the reflected wave intensity in the yz plane under a frequency of 1.05 THz in the structure of Embodiment 10.

[0071] Figure 35 This is a top view of the structure fabricated in Example 11.

[0072] Figure 36 This is a graph showing the calculated results of the angular distribution of the reflected wave intensity in the xz plane under a frequency of 100 GHz in the structure of Embodiment 11.

[0073] Figure 37 This is a graph showing the calculated results of the angular distribution of the reflected wave intensity in the yz plane under a frequency of 100 GHz in the structure of Embodiment 11. Detailed Implementation

[0074] Hereinafter, exemplary embodiments of the present invention (sometimes referred to as these embodiments) will be described, but the present invention is not limited to these embodiments.

[0075] In this disclosure, various measurements are performed based on the methods described in the specification, particularly the methods described in the embodiments. In this specification, the upper or lower limit of a phased numerical range can be replaced by the upper or lower limit of another corresponding phased numerical range, particularly by the corresponding values ​​described in the embodiments. Furthermore, in this specification, "process" is not only an independent process, but is also included in this terminology as long as the function of the process can be achieved, even when it cannot be clearly distinguished from other processes. The structures (scale, shape, length, etc.) shown in the accompanying drawings are sometimes exaggerated for further clarity.

[0076] <Structures with three-dimensional curved surfaces>

[0077] In this embodiment, a three-dimensional surface refers to a surface that cannot be formed by deforming a plane (i.e., it is not a developable surface).

[0078] The structure of this embodiment is a three-dimensional curved surface structure, which includes a metal layer, a dielectric, and a metal pattern area on the surface of the dielectric. Furthermore, the structure of this embodiment sequentially comprises a metal layer, a dielectric, and a metal pattern area on the surface of the dielectric.

[0079] [Metallic layer]

[0080] The metal constituting the metal layer in this embodiment is not particularly limited, and examples include silver, copper, gold, aluminum, magnesium, zinc, cobalt, nickel, lithium, platinum, palladium, tin, chromium, lead, hafnium, zirconium, bismuth, manganese, titanium, molybdenum, antimony, indium, gallium, calcium, rhodium, iridium, sodium, tungsten, ruthenium, potassium, cadmium, osmium, rubidium, tantalum, strontium, thorium, niobium, protactinium, rhenium, vanadium, barium, arsenic, antimony, lutetium, yttrium, lanthanum, neodymium, thulium, holmium, dysprosium, and germanium.

[0081] From the perspective of ease of processing and improved electromagnetic wave transmittance, the metal constituting the metal layer in this embodiment is preferably silver, copper, gold, platinum, aluminum, nickel, and iron, more preferably silver, copper, gold, platinum, and aluminum, even more preferably silver, copper, and aluminum, and particularly preferably copper. From the same perspective, copper oxide is preferred as the metal compound.

[0082] From the perspective of improving reflectivity, the thickness of the metal layer in this embodiment is preferably 50 nm or more, or 100 nm or more. From the perspective of ease of processing, the thickness of the metal layer in this embodiment is preferably 200 μm or less, or 100 μm or less. It should be noted that the thickness of the metal layer in this embodiment was measured using the method described in the examples.

[0083] [Dielectric]

[0084] In this embodiment, the dielectric is a layer disposed on a metal layer. In one embodiment, the dielectric may be in contact with the metal layer, or it may be separated from the metal layer by other layers without contact.

[0085] From the perspective of generating a desired phase shift in electromagnetic waves, for example, in electromagnetic wave control applications, the relative permittivity of the dielectric in this embodiment is preferably 2 or more, or 2.5 or more, or 3 or more. From the perspective of reducing energy loss of electromagnetic waves, for example, in electromagnetic wave control applications, the relative permittivity of the dielectric in this embodiment is preferably 100 or less, or 50 or less, or 30 or less, or 10 or less, or 5 or less.

[0086] It should be noted that the relative permittivity of the dielectric was determined using the method described in the examples.

[0087] From the perspective of suppressing changes in dielectric constant and size caused by water absorption, as well as the attenuation of transmitted electromagnetic waves, the water absorption rate of the dielectric is preferably below 0.2, or below 0.15, or below 0.1.

[0088] It should be noted that the water absorption rate of the dielectric was determined using the method described in the examples.

[0089] Ceramic and resin can be used as the dielectric in this embodiment.

[0090] As ceramics, examples include oxides, carbides, nitrides, borides, and fluorides of one or more elements selected from silicon, silver, copper, gold, aluminum, magnesium, zinc, cobalt, nickel, lithium, platinum, palladium, tin, chromium, lead, hafnium, zirconium, bismuth, manganese, titanium, molybdenum, antimony, indium, gallium, calcium, rhodium, iridium, sodium, tungsten, ruthenium, potassium, cadmium, osmium, rubidium, tantalum, strontium, thorium, niobium, protactinium, rhenium, vanadium, barium, arsenic, antimony, lutetium, yttrium, lanthanum, neodymium, thulium, holmium, dysprosium, and germanium.

[0091] From the perspective of ease of forming into three-dimensional curved surfaces, oxides, carbides, nitrides, borides, and fluorides of silicon, copper, aluminum, and magnesium are particularly preferred.

[0092] Examples of resins include polyimide (PI), liquid crystal polyester (LCP), polyesters (polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polybutylene terephthalate (PBT), etc.), polyethersulfone (PES), polycarbonate (PC), polyvinyl alcohol (PVA), polyvinyl butyral (PVB), polyacetal (POM), polyarylate (PAR), polyamide (PA) (PA6, PA66, etc.), polyamide-imide (PAI), polyether-imide (PEI), polyphenylene ether (PPE), modified polyphenylene ether (m-PPE), polyphenylene sulfide (PPS), polyetherketone (PEK), polyphthalamide (PPA), polyether nitrile (PENt), polybenzimidazole (PBI), polycarbodiimide, polysiloxane, polymethacrylamide, nitrile rubber, acrylic rubber, and polytetrafluoroethylene. Epoxy resins, phenolic resins, melamine resins, urea resins, polymethyl methacrylate resins (PMMA), polybutene, polypentene, ethylene-propylene copolymers, ethylene-butene-diene copolymers, polybutadiene, polyisoprene, ethylene-propylene-diene copolymers, butyl rubber, polymethylpentene (PMP), polystyrene (PS), styrene-butadiene copolymers, polyethylene (PE), polyvinyl chloride (PVC), polyvinylidene fluoride (PVDF), polyether ether ketone (PEEK), phenolic varnish, benzocyclobutene, polyvinylphenol, polychloroprene, polyoxymethylene, polysulfone (PSF), polyphenylene sulfone resin (PPSU), cyclic olefin polymers (COP), acrylonitrile-butadiene-styrene resins (ABS), acrylonitrile-styrene resins (AS), polytetrafluoroethylene resins (PTFE), and polychlorotrifluoroethylene (PCTFE), etc.

[0093] In particular, PI, LCP and epoxy resins are preferred from the perspective of ease of molding into three-dimensional curved surfaces.

[0094] In this embodiment, from the perspective of easily achieving the desired phase shift, the thickness of the dielectric is preferably 75 nm or more, or 1 μm or more, or 3 μm or more, or 10 μm or more, and from the same perspective, it is preferably 43 mm or less, or 20 mm or less, or 8 mm or less.

[0095] It should be noted that the thickness of the dielectric was measured using the method described in the examples.

[0096] [Metal Pattern Area]

[0097] In this embodiment, the metal pattern area is disposed on the surface of the dielectric. In this disclosure, multiple metal patterns can be disposed on the metal, and their shape and size can be selected as needed. Alternatively, the metal pattern in this embodiment can also be obtained by forming a pattern on the metal.

[0098] In one embodiment, the shape of the metal pattern is preferably rectangular or circular, and the size of the metal pattern is preferably more than 1 / 100 and less than 1 / 2 of the wavelength of the incident electromagnetic wave on one side (e.g., in the case where the shape of the metal pattern is rectangular) and in the case where the shape of the metal pattern is circular.

[0099] The metal patterned region in this embodiment is composed of superatoms as described later in this embodiment.

[0100] In this disclosure, the area of ​​the metal pattern region in this embodiment refers to the area surrounding the outer perimeter of the metal pattern region.

[0101] From the perspective of enabling the electromagnetic waves emitted by the three-dimensional curved structure of this embodiment to cover a wide area, the area of ​​the metal pattern region in this embodiment is preferably 0.09 mm². 2 Above, or 0.36mm 2 Above or 9mm 2 That's all. Furthermore, from the perspective of ease of processing, the area of ​​the metal pattern region in this embodiment is preferably 20m². 2 Below, or 5m 2 Below, or 0.02m 2 Below, or 1100mm 2 Below, or 400mm 2 Below, or 110mm 2 the following.

[0102] In this embodiment, the area of ​​the metal pattern region is preferably 0.09 mm². 2 Above 20m 2 The following, or more preferably, is 0.36mm 2 The above 5m 2 The following, particularly preferred, is 9mm. 20.02m above 2 the following.

[0103] In one embodiment, from the perspective of enabling electromagnetic waves emitted by the structure with a three-dimensional curved surface of this embodiment to cover a wide area, the area of ​​the metal pattern region in this embodiment is 100 mm². 2 Above, or 1000mm 2 Above, or 2500mm 2 Above, or 5000mm 2 Above, or 10000mm 2 That's all. Additionally, in one embodiment, from the perspective of ease of processing, the area of ​​the metal pattern region is 100m². 2 Below, or 10m 2 Below, or 1m 2 Below, or 0.5m 2 Below, or 0.25m 2 the following.

[0104] The area of ​​the metal pattern region in this embodiment is measured by the following method.

[0105] The area of ​​the metal pattern region in this embodiment can also be calculated by measuring the characteristic length of the surface surrounding the outer periphery of the metal pattern region (in one way, the longitudinal and transverse lengths of the metal pattern region) using an optical microscope, without any particular limitation.

[0106] In one approach, the area of ​​the metal pattern region is calculated by multiplying the longitudinal and transverse lengths of the metal pattern region, respectively.

[0107] The metal constituting the metal pattern area in this embodiment is not particularly limited, and examples include silver, copper, gold, aluminum, magnesium, zinc, cobalt, nickel, lithium, platinum, palladium, tin, chromium, lead, hafnium, zirconium, bismuth, manganese, titanium, molybdenum, antimony, indium, gallium, calcium, rhodium, iridium, sodium, tungsten, ruthenium, potassium, cadmium, osmium, rubidium, tantalum, strontium, thorium, niobium, protactinium, rhenium, vanadium, barium, arsenic, antimony, lutetium, yttrium, lanthanum, neodymium, thulium, holmium, dysprosium, and germanium.

[0108] From the perspective of ease of processing and improved electromagnetic wave transmittance, the metal pattern area of ​​this embodiment preferably includes silver, copper, gold, platinum, aluminum, nickel and iron, more preferably includes silver, copper, gold, platinum and aluminum, and even more preferably includes silver, copper and aluminum.

[0109] (Additional layer)

[0110] In addition to the dielectric and the metal patterned area present on the surface of the dielectric, the structure with a three-dimensional curved surface in this embodiment may also include additional layers.

[0111] For example, the structure with a three-dimensional curved surface in this embodiment can be configured with an antioxidant layer in the form of covering the exposed metal pattern area. Examples of antioxidant layers include silicone resins, fluoropolymers, butyral resins, polyurethane resins, epoxy resins, acrylic resins, modified polyesters, polyamide resins, polyolefin resins, and fluorinated acrylic resins. The presence of an antioxidant layer prevents the metal pattern area from oxidizing due to contact with oxygen in the air, thus enabling longer-term electromagnetic wave control performance.

[0112] [Supreme Atoms]

[0113] In this disclosure, metaatoms refer to the metal patterns that constitute the metal pattern regions of this embodiment.

[0114] The shape of a metaatom is not particularly limited; for example, it can be a polyhedron. A metaatom can have cavities inside. The surface of a metaatom can be either planar or curved.

[0115] In one aspect of the invention, from the viewpoint of improving the adhesion to the adjacent dielectric and the antioxidant layer additionally provided to prevent oxidation of metaatoms, it is preferable that the surface of the metaatoms has a certain periodicity. In this disclosure, the surface of the metaatoms having a certain periodicity means, for example, that the same structure, such as a structure composed of concave and convex features (hereinafter referred to as a convex-concave structure) and a step-like structure, is continuous on the surface of the metaatoms.

[0116] In one embodiment, from the above-mentioned aspects, a certain period of the metaatomic surface (e.g., the period of the convex-concave structure and the step structure) is preferably 3 μm or more, or 5 μm or more, or 10 μm or more, and from the above-mentioned aspects, preferably 1000 μm or less, or 300 μm or less, or 150 μm or less.

[0117] In this embodiment, the periodicity of the surface of the metaatoms is determined by obtaining a microscope image of the cross-section of the structure using an electron microscope and then detecting the surface of the metaatoms.

[0118] In this disclosure, a concave-convex structure refers to a structure in which the height difference between the convex and concave portions is 0.01 μm or more. The boundary between the convex and concave portions can be a clearly defined step or a wavy concave-convex structure composed of smooth inclines.

[0119] From the perspective of improving the adhesion between the protrusion and the adjacent dielectric and the additional antioxidant film provided to prevent oxidation of meta atoms, the height difference between the protrusion and the concave part is preferably 0.01 μm or more, or 0.05 μm or more, or 0.1 μm or more. From the perspective of improving the mechanical strength of meta atoms, it is preferably 1 μm or less, or 0.5 μm or less, or 0.2 μm or less.

[0120] In this disclosure, a stepped structure refers to a structure in which the height of the steps periodically increases or decreases. From the perspective of improving the adhesion with the adjacent dielectric and the antioxidant film additionally provided to prevent oxidation of metaatoms, the height of the steps is preferably 0.01 μm or more, or 0.05 μm or more, or 0.1 μm or more. From the perspective of improving the mechanical strength of metaatoms, it is preferably 1 μm or less, or 0.5 μm or less, or 0.2 μm or less.

[0121] Since superatoms do not have a particularly defined shape, the diameter of the smallest containing sphere of the superatom is used when representing the size of the superatom. In this disclosure, the smallest containing sphere of the superatom refers to the sphere with the smallest diameter that contains the superatom.

[0122] From the perspective of efficiently exciting surface plasmons by incident electromagnetic waves, the diameter of the smallest containment sphere of the metaatom is 3 μm or more and 430 mm or less relative to the wavelength of the incident electromagnetic wave, preferably 3 μm or more and 100 mm or less, or 50 μm or more and 1.5 mm or less. The diameter of the smallest containment sphere of the metaatom is preferably 10 μm or more, or 30 μm or more, or 50 μm or more, or 75 μm or more, or 100 μm or more relative to the wavelength of the incident electromagnetic wave. From the above perspective, it is preferably 200 mm or less, or 100 mm or less, or 85 mm or less, or 50 mm or less, or 15 mm or less, or 4 mm or less, or 2 mm or less, or 1.5 mm or less, or 1 mm or less, or 500 μm or less, or 400 μm or less.

[0123] In one approach, if there is a deviation in the numerical value of the diameter of the minimum containing sphere of the superatom, the average of the minimum and maximum diameters can be used as the diameter of the minimum containing sphere of the superatom.

[0124] The diameter of the smallest containment sphere of the metaatom was determined by taking a microscopic image of the metaatom using an optical microscope and then calculating it using image processing in Image J.

[0125] The diameter of the smallest containing sphere of a metaatom can be adjusted appropriately by changing the laser irradiation area, etc.

[0126] The size of the metaatoms can be appropriately designed according to the wavelength of the electromagnetic wave incident on the structure with a three-dimensional curved surface. The incident electromagnetic wave can be a microwave to a terahertz wave, with wavelengths ranging from 10 μm to 430 mm or from 30 μm to 1000 mm, for example. From the perspective of efficiently exciting surface plasmons by the incident electromagnetic wave, the diameter of the smallest containing sphere of the metaatoms is preferably 0.02 times or more, or 0.03 times or more, or 0.05 times or more relative to the wavelength of the incident electromagnetic wave. From the above perspective, it is preferably less than 1 time, or less than 0.7 times, or less than 0.5 times relative to the wavelength of the incident electromagnetic wave.

[0127] From the perspective of the ease of formation of metaatoms, the volume resistivity of metaatoms is preferably 1.5 × 10⁻⁶. -8 Ω From the perspective of suppressing the energy of electromagnetic waves incident on the electromagnetic wave control element from being converted into heat energy and attenuated, a value of 1×10 m or more is preferred. -3 Ω Less than m, or 1×10 -4 Ω Less than m, or 1×10 -5 Ω Less than m, or 1×10 -6 Ω Below m.

[0128] There are no particular limitations on the metallic elements that make up the superatoms. Examples include silver, copper, gold, aluminum, magnesium, zinc, cobalt, nickel, lithium, platinum, palladium, tin, chromium, lead, hafnium, zirconium, bismuth, manganese, titanium, molybdenum, antimony, indium, gallium, calcium, rhodium, iridium, sodium, tungsten, ruthenium, potassium, cadmium, osmium, rubidium, tantalum, strontium, thorium, niobium, protactinium, rhenium, vanadium, barium, arsenic, antimony, lutetium, yttrium, lanthanum, neodymium, thulium, holmium, dysprosium, and germanium.

[0129] From the perspective of minimizing the attenuation of surface plasmons excited by electromagnetic waves, silver, copper, gold, platinum, aluminum, nickel, and iron are preferred as metallic elements constituting metaatoms; silver, copper, gold, platinum, and aluminum are more preferred; and silver, copper, and gold are even more preferred. Furthermore, from the perspective of improving the adhesion between metaatoms and adjacent dielectrics, and the antioxidant layer additionally provided to prevent oxidation of metaatoms, copper is preferred as a metallic element constituting metaatoms.

[0130] In one embodiment of the present invention, the metaatom comprises a metal and carbon. Furthermore, from the viewpoint of improving the adhesion between the metaatom and the dielectric, the carbon content of the metaatom relative to the metal element (in one embodiment, the carbon / metal element concentration ratio of the metaatom) is preferably 0.05 or more, or 0.1 or more, or 0.5 or more, or 1.0 or more, or 1.5 or more, or 2.0 or more. From the viewpoint of minimizing the attenuation of surface plasmons excited by electromagnetic waves, the carbon / metal element concentration ratio of the metaatom is 6.0 or less, or 5.5 or less, or 5.0 or less.

[0131] As a method for controlling the carbon / metal elemental concentration ratio of metaatoms to the aforementioned range, one example is the method of producing metaatoms by irradiating a composition in which the mixing ratio of metal compounds and organic compounds is adjusted with energy such as heat, plasma, or electromagnetic waves.

[0132] The carbon / metal elemental concentration ratio of the metaatoms can be determined using EDX analysis.

[0133] From the perspective of efficiently exciting surface plasmons by incident electromagnetic waves, the thickness of the metaatoms in this embodiment is preferably 50 nm or more, or 100 nm or more. Similarly, the thickness of the metaatoms in this embodiment is preferably 300 μm or less, or 200 μm or less, or 100 μm or less. It should be noted that the thickness of the metaatoms is measured using the method described in the examples.

[0134] (Metal compound layer)

[0135] From the perspective of improving the reflectivity of the structure, the structure of this embodiment preferably has a metal oxide layer (in one embodiment, a metal compound layer) at the boundary between the metaatoms and the dielectric layer. Furthermore, from the perspective of improving the reflectivity of the structure, the metaatoms of this embodiment preferably have a metal compound layer inside them.

[0136] From the perspective of improving the reflectivity of the structure, the thickness of the metal compound layer in this embodiment is preferably 40 nm or more, or 50 nm or more, or 75 nm or more, or 100 nm or more. Similarly, the thickness of the metal compound layer in this embodiment is preferably 10 μm or less, or 5 μm or less, or 1 μm or less. It should be noted that the thickness of the metal compound layer in this embodiment is measured using the method described in the examples.

[0137] From the perspective of improving reflectivity, the proportion of the metal compound layer in the thickness of the metaatomic layer is preferably 0.01 or more, or 0.1 or more, 0.15 or more, or 0.2 or more. Similarly, it is preferably 0.5 or less, or 0.3 or less.

[0138] The thickness of the metal compound layer inside the metaatoms can be adjusted appropriately by means of laser irradiation intensity and other operations.

[0139] The metal compound constituting the metal compound layer in this embodiment is not particularly limited, and examples include oxides or nitrides of silver, copper, gold, aluminum, magnesium, zinc, cobalt, nickel, lithium, platinum, palladium, tin, chromium, lead, hafnium, zirconium, bismuth, manganese, titanium, molybdenum, antimony, indium, gallium, calcium, rhodium, iridium, sodium, tungsten, ruthenium, potassium, cadmium, osmium, rubidium, tantalum, strontium, thorium, niobium, protactinium, rhenium, vanadium, barium, arsenic, antimony, lutetium, yttrium, lanthanum, neodymium, thulium, holmium, dysprosium, and germanium.

[0140] From the perspective of being stable as a metallic compound and capable of being reduced to a metal with relatively little energy, copper is preferred as the metallic element constituting the metallic compound layer. Similarly, copper oxide is preferred as the metallic compound. From the perspective of improving the reflectivity of the structure, a layer comprising a copper oxide layer is preferred as the metallic compound layer existing within the metaatoms.

[0141] The metals constituting the metaatomic and metallic compound layers of this embodiment preferably contain copper, from the perspective of efficiently exciting surface plasmons by incident electromagnetic waves.

[0142] [Resin Layer]

[0143] The structure in this embodiment preferably has a resin layer on the outer side of the metal pattern area.

[0144] Examples of resin layers used in this embodiment include silicone resins, fluororesins, butyral resins, polyurethane resins, epoxy resins, acrylic resins, modified polyesters, polyamide resins, polyolefin resins, fluorinated acrylic resins, and polyimides.

[0145] The presence of the resin layer in this embodiment prevents oxidation of the metal pattern area due to contact with oxygen in the air, thus enabling longer-term electromagnetic wave control performance. Furthermore, it reduces the amount of water penetrating into the structure of this embodiment and suppresses water absorption by the dielectric layer, thereby preventing the reduction in adhesion between the metal pattern layer and the dielectric layer caused by dimensional changes due to water absorption.

[0146] In particular, when the dielectric layer in this embodiment is formed of a resin with low water absorption, such as modified polyphenylene ether (m-PPE), the amount of water absorbed into the dielectric layer is suppressed in combination with the effect brought about by the presence of the resin layer, and electromagnetic wave control performance can be maintained for a longer period of time.

[0147] (Operating frequency)

[0148] The operating frequency of the structure with a three-dimensional curved surface in this embodiment can be from the visible light band to the terahertz band. From the perspective of suitability for high-speed communication applications, the operating frequency of the structure in this embodiment is preferably 0.3 GHz or higher, or 0.7 GHz or higher, or 1.5 GHz or higher, or 3.6 GHz or higher, or 27 GHz or higher, or 92 GHz or higher, or 152 GHz or higher, or 287 GHz or higher. From the perspective of suppressing electromagnetic wave attenuation, the operating frequency of the structure in this embodiment is preferably 10 THz or lower, or 5 THz or lower, or 1 THz or lower.

[0149] The operating frequency of the structure in this embodiment is preferably 0.3 GHz or higher and 10 THz or lower, more preferably 0.7 GHz or higher and 5 THz or lower.

[0150] Electromagnetic wave transceiver system

[0151] One aspect of the present invention provides an electromagnetic wave transceiver system comprising a structure having a three-dimensional curved surface as described in this embodiment and an electromagnetic wave oscillation antenna. The form and shape of the electromagnetic wave oscillation antenna are not particularly limited and can be appropriately selected according to the purpose. For example, a microstrip antenna can be used as an electromagnetic wave oscillation antenna.

[0152] <Manufacturing Methods for Structures with Three-Dimensional Curved Surfaces>

[0153] The manufacturing method of the structure in this embodiment is a method for manufacturing a structure including a dielectric and a metal pattern region on the surface of the dielectric, which includes a step of forming a metal pattern region on the surface of the dielectric.

[0154] [Process for forming the metal pattern area]

[0155] In this process, a metallic pattern area is formed on the surface of a dielectric. One method for forming the metallic pattern area is to coat the dielectric surface with a composition containing, for example, a metal precursor to form a coating layer, and then selectively irradiate the coating layer with light energy (photoforming method).

[0156] The metal precursor contained in the coating layer can be microparticles, with an average particle size of 1 nm to 100 nm, more preferably 1 nm to 50 nm, and even more preferably 1 nm to 20 nm. The smaller the particle size of the metal precursor, the more the particles can thermally adhere to each other through light irradiation, and the smaller the attenuation of the resonant electromagnetic waves in the metal pattern, which is preferred.

[0157] In photolithography, light irradiation is used as the energy source. Flash methods using xenon discharge tubes or lasers can be employed as the light source. These methods involve short-duration exposure to high-intensity light, rapidly raising the temperature of the dielectric layer to a high temperature for lithography. This process involves the reduction, sintering, integration, and decomposition of organic matter in the coating layer containing the metal precursor, forming a metallic pattern. In photolithography using laser irradiation, lithography and patterning can be achieved in a single step by irradiating the coating layer containing the metal precursor with a laser.

[0158] The flash method refers to the instantaneous discharge of the charge stored in a capacitor using a xenon discharge tube. This method generates a large amount of pulsed light, which is used to irradiate the coating layer of the composition containing the metal precursor, instantly heating the metal precursor on and / or within the dielectric layer to a high temperature, causing it to change into a metallic pattern. The exposure can be adjusted by the light intensity, irradiation time, irradiation interval, and number of exposures.

[0159] Although the light source is different, the same effect as flash lighting can be achieved using a laser light source. In the case of a laser, in addition to adjusting the flash lighting method, there is also freedom in wavelength selection; the emission wavelength can be selected by considering the light absorption wavelength of the coating layer containing the metal precursor. Furthermore, exposure can be performed by beam scanning, allowing for easy adjustment of the exposure range, such as selecting exposure of the entire coating layer or partial exposure.

[0160] As for the types of lasers, YAG (yttrium aluminum garnet) lasers, YVO (yttrium vanadate) lasers, Yb (ytterbium) lasers, semiconductor (GaAs, GaAlAs, GaInAs) lasers, and carbon dioxide lasers can be used. Not only can the fundamental wave be used, but higher harmonics can also be extracted as needed.

[0161] Especially when using lasers, the emission wavelength is preferably between 300 nm and 1500 nm, for example, preferably 355 nm, 405 nm, 445 nm, 450 nm, 532 nm, 1056 nm, etc. From the absorption region of the coating layer of the composition containing the metal precursor, laser wavelengths of 355 nm, 405 nm, 445 nm, 450 nm, and / or 532 nm are particularly preferred. By using lasers, desired patterns can be fabricated three-dimensionally and freely.

[0162] By selecting the wavelengths described above, desired voids can be formed, making it easy to fabricate metal-containing films with the desired porosity. The porosity of the metal-containing film can be controlled by adjusting the output power and speed of the laser irradiating the coating film of the metal precursor composition. For example, slowing down the laser scanning speed helps to reduce the porosity.

[0163] Selective laser irradiation can be achieved, for example, by irradiating a coating film of a composition containing a metal precursor through a mask in a laser manner, or by directly drawing a desired pattern on the coating film by scanning a laser beam in a laser manner. The irradiated surface can be planar or non-planar, for example, it can be a shell with a three-dimensional substrate.

[0164] The exposure amount can be adjusted by the laser intensity, irradiation time, laser irradiation interval, and number of irradiations. In one embodiment, preferably, in the laser-irradiated area of ​​the coating film containing the metal precursor composition, a portion of the coating film remains as a metal compound layer at the boundary with the dielectric layer. The metal compound layer functions as a dielectric, thus improving reflectivity.

[0165] (Cleaning process)

[0166] After laser irradiation, a cleaning process can be performed using a suitable cleaning solution to remove the unburned areas. In this case, only the burned areas remain on the dielectric surface. Alternatively, a cleaning process can be omitted, leaving the unburned areas remaining along with the burned areas.

[0167] As a cleaning fluid used during cleaning, a solvent that disperses or dissolves metal compounds (such as copper oxide) can be used.

[0168] Specific examples include water, propylene glycol monomethyl ether acetate, 3-methoxy-3-methyl-butyl acetate, ethoxyethyl propionate, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monopropyl ether, propylene glycol tert-butyl ether, dipropylene glycol monomethyl ether, ethylene glycol butyl ether, ethylene glycol ethyl ether, ethylene glycol methyl ether, ethylene glycol, 1,2-propanediol, 1,3-butanediol, 2-pentanediol, 2-methylpentane-2,4-diol, 2,5-hexanediol, 2,4-heptanediol, 2-ethylhexane-1,3-diol, diethylene glycol, hexanediol, octanediol, triethylene glycol, tri-1,2-propanediol, glycerol, ethylene glycol monohexyl ether, diethylene glycol... Alcohol monoethyl ether, diethylene glycol monobutyl ether, ethylene glycol monobutyl acetate, diethylene glycol monoethyl ether acetate, methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol, 2-butanol, tert-butanol, n-pentanol, isopentanol, 2-methylbutanol, 2-pentanol, tert-pentanol, 3-methoxybutanol, n-hexanol, 2-methylpentanol, 1-hexanol, 2-hexanol, 2-ethylbutanol, 1-heptanol, 2-heptanol, 3-heptanol, n-octanol, 2-ethylhexanol, 2-octanol, n-nonanol, 2,6-dimethyl-4-heptanol, n-decanol, cyclohexanol, methylcyclohexanol, 3,3,5-trimethylcyclohexanol, benzyl alcohol, diacetone alcohol, and acetone, etc.

[0169] Especially when the coating layer of the composition containing the metal precursor contains a dispersant, the above-mentioned solvent is preferred because it can effectively wash away the metal precursor. Water, ethanol, butanol, isopropanol, and acetone are particularly preferred as solvents. It should be noted that a dispersant may be added to the above-mentioned cleaning solution. A phosphorus-containing organic compound is preferred as a dispersant.

[0170] (Optional plating process)

[0171] It can perform a plating process on metal patterns after laser irradiation.

[0172] The metal-containing film after the laser irradiation process preferably has a porosity of 0.5% by volume or more. By setting this porosity, the plating solution can easily penetrate in subsequent plating processes, resulting in good adhesion and thus good bonding. More preferably, the porosity is 0.7% by volume or more, more preferably 1.0% by volume or more, more preferably 1.5% by volume or more, more preferably 2.0% by volume or more, and more preferably 2.5% by volume or more. Furthermore, from the perspective of the adhesion between the copper-containing film and the substrate, the porosity is preferably 60% by volume or less, more preferably 58% by volume or less, more preferably 55% by volume or less, more preferably 53% by volume or less, and more preferably 51% by volume or less.

[0173] <Degreasing process>

[0174] In one embodiment, the method disclosed herein may further include a degreasing step of degreasing the metal-containing film. Examples of degreasing methods include UV degreasing and wet degreasing. The degreasing step accelerates the growth rate of subsequent plating, increasing productivity. Furthermore, this step helps reduce the porosity of the plated metal pattern.

[0175] From the perspective of the interlayer tightness of the structure, the degreasing process is preferably carried out by immersing the structure in a degreasing solution containing an amino compound. Examples of amino-containing compounds include amino acids such as alanine, arginine, asparagine, cysteine, glutamine, glycine, histidine, isoleucine, leucine, lysine, methionine, phenylalanine, proline, serine, threonine, tryptophan, tyrosine, and valine; alkylamines such as methylamine, dimethylamine, ethylamine, trimethylamine, diethylamine, triethylamine, propylamine, isopropylamine, and diisopropylamine; alkanolamines such as 2-aminoethanol, diethanolamine, triethanolamine, N-methylethanolamine, and N,N-dimethylethanolamine; polyamines such as ethylenediamine, diethylenetriamine, tetraethylenepentamine, tri(hydroxymethyl)aminomethane, m-phenylenediamine, p-phenylenediamine, and 1,3-bis(aminomethyl)cyclohexane; aminosulfonic acids such as taurine; aminothiols such as 2-aminoethanethiol; and nitrogen-containing heterocyclic compounds such as 3-pyridinemethylamine and 3-pyridinemethanol. From the perspective of promoting the growth rate of the coating, 2-aminoethanol is particularly preferred.

[0176] Degreasing solutions can be commercially available products. Specifically, examples include ALC-009 from Uemura Industries, Ltd. (which contains 2-aminoethanol as an amino compound) and Cleaner Securigant 902 from Atotech Japan Co., Ltd. (which contains 2-aminoethanol as an amino compound).

[0177] Regarding the concentration of the amino-containing compound in the degreasing solution, from the perspective of removing substances that hinder the plating reaction, it is preferably 5 mmol / L or more, more preferably 10 mmol / L or more, and even more preferably 20 mmol / L or more. Furthermore, from the perspective of promoting the plating reaction, the concentration of the amino-containing compound in the degreasing solution is preferably 100 mmol / L or less, more preferably 90 mmol / L or less, and even more preferably 80 mmol / L.

[0178] Regarding the immersion time of the structure in the degreasing solution, from the perspective of promoting the growth rate of the plating, it is preferably 1 minute or more, more preferably 2 minutes or more. Furthermore, from the perspective of reducing damage to the dielectric, the immersion time of the structure in the degreasing solution is preferably 15 minutes or less, more preferably 10 minutes or less. From the perspective of uniform degreasing, immersion under stirring is preferred.

[0179] To enhance the growth rate promotion effect of the plating, the immersion temperature is preferably 15°C or higher, more preferably 30°C or higher, and even more preferably 40°C or higher. Furthermore, from the perspective of reducing damage to the dielectric, the immersion temperature is preferably 70°C or lower, more preferably 60°C or lower.

[0180] After the degreasing process, the structure is preferably cleaned with a cleaning solution. The cleaning solution is preferably water. The temperature of the cleaning solution is preferably 15°C or higher, more preferably 20°C or higher. Furthermore, from the perspective of reducing damage to the dielectric, the temperature of the cleaning solution is preferably 70°C or lower, more preferably 60°C or lower.

[0181] It is preferable to perform the plating process after cleaning the structure.

[0182] <Plating Process>

[0183] In this process, the metal-containing film, whether or not it has undergone a degreasing process, is plated. By performing electrolytic or electroless plating on the metal-containing film (in one way, a metal pattern) of the structure obtained as described above, a plating layer (e.g., a copper plating layer) of a desired thickness is obtained.

[0184] In one embodiment, the plating is electroless plating. In another embodiment, electroless plating of the metal-containing film easily improves conductivity. Electroless plating allows the formation of metal patterns consisting of a metal compound layer and a plating layer. Electroless plating can easily form thick metal patterns, making it particularly advantageous when manufacturing structures for applications requiring high current. In one embodiment, electroless plating is preferred from the perspective of broad applicability to patterns, especially for patterned metal patterns created using lasers.

[0185] Electroless plating can utilize common electroless plating methods. For example, it can be performed in conjunction with degreasing or cleaning processes. The plating bath can be, for example, a plating solution containing copper ions and a reducing agent. By immersing the structure in the plating solution while simultaneously bubbling air, the copper ions in the solution are reduced, and copper precipitates onto the surface of the reduced copper layer, forming a copper plating layer.

[0186] As an electroless plating bath, plating solutions containing, for example, CuSO4 as a copper ion source, EDTA (ethylenediaminetetraacetic acid) or Rochelle salt as a complexing agent, and formaldehyde (CH2O), potassium tetrahydrogenate, dimethylamine borane, glyoxylic acid or hypophosphino acid as a reducing agent can be used.

[0187] Commercially available plating solutions include Thru-cup PEA-6 and Thru-cup ELC-SP from Uemura Industries, Ltd.; Melplate CU-390 and Melplate CU-5100P from Meltex Corporation; OPC Copper HFS, OPC Copper NCA, and ATS ADD COPPER IW from Okuno Pharmaceutical Industries, Ltd.; CUPOSIT328 and C4500 from Rohm and Haas Corporation; Atotech MVTP1 and PrintganthUPlus from Atotech Corporation; and Cu-150 and Cu-510 from MacDermid Corporation of Japan.

[0188] Electroless plating solutions are used in electroless plating. EDTA (ethylenediaminetetraacetic acid) is preferably included in the electroless plating solution. EDTA acts as a complexing agent, forming highly stable complexes with copper ions. Therefore, it is believed to suppress side reactions in the plating bath and help prevent coating peeling by ensuring stable and uniform plating deposition. This contributes to the fabrication of structures with excellent interlayer adhesion. Furthermore, since EDTA is stable in high-temperature solutions, it also helps to accelerate the plating process.

[0189] The plating bath used for electroless plating may further contain surfactants.

[0190] From the perspective of fully utilizing the advantages brought by EDTA, the amount of EDTA in the electroless plating solution is preferably 7 g / L or more, or 10 g / L or more, or 15 g / L or more. From the perspective of reducing impurities in the plating precipitates and reducing resistance, it is preferably 50 g / L or less, or 45 g / L or less, or 40 g / L or less.

[0191] Furthermore, the temperature of the electroless plating bath is preferably 25–80°C, and more preferably 30–70°C or 35–65°C, as faster plating growth can be expected. The plating time is preferably 5–60 minutes, more preferably 5–50 minutes, and even more preferably 10–40 minutes.

[0192] Electroless plating is preferably performed using a plating solution with a copper concentration in the range of 1.5 g / L to 5.0 g / L. To improve the plating speed, a concentration of 1.5 g / L or higher is preferred; from the perspective of the uniformity of the plating film, a concentration of 5.0 g / L or lower is preferred. The copper concentration is further preferably 1.5 g / L to 4.0 g / L, further preferably 1.8 g / L to 3.5 g / L, and further preferably 2.0 g / L to 3.0 g / L.

[0193] In one approach, electroplating can be performed after electroless plating. Electroplating can utilize common electroplating methods. For example, electrodes and a metal pattern to be plated are placed in a solution (plating bath) containing metal ions (e.g., copper ions). Then, a direct current is applied between the electrodes and the metal pattern by an external direct current power supply. In another approach, current can be applied to the metal pattern by connecting a clamp (e.g., a clip) connected to one of the electrodes of the external direct current power supply to the metal pattern on the dielectric. As a result, metal is deposited on the surface of the metal pattern on the dielectric through the reduction of metal ions, forming a plated metal layer.

[0194] For electroplating baths, copper sulfate baths, copper fluoroborate baths, copper cyanide baths, and copper pyrophosphate baths can be used. From the perspectives of safety and productivity, copper sulfate baths and copper pyrophosphate baths are preferred.

[0195] As a copper sulfate plating bath, a sulfuric acidic copper sulfate plating bath containing copper sulfate pentahydrate, sulfuric acid, and chlorine can be suitably used, for example. The concentration of copper sulfate pentahydrate in the copper sulfate plating bath is preferably 50 g / L or more, or 100 g / L or more, preferably 300 g / L or less, or 200 g / L or less. The concentration of sulfuric acid is preferably 40 g / L or more, or 80 g / L or more, preferably 160 g / L or less, or 120 g / L or less. The solvent in the plating bath is usually water.

[0196] The temperature of the plating bath is preferably above 20°C or 30°C, and more preferably below 60°C or 50°C. The current density during electrolytic treatment is preferably 1 A / dm³. 2 Above, or 2A / dm 2 The above is preferably 15A / dm. 2 Below, or 10A / dm 2 the following.

[0197] The copper pyrophosphate plating bath is preferably a plating bath containing copper pyrophosphate and potassium pyrophosphate. The concentration of copper pyrophosphate in the copper pyrophosphate plating bath is preferably 60 g / L or more, or 70 g / L or more, preferably 110 g / L or less, or 90 g / L or less. The concentration of potassium pyrophosphate is preferably 240 g / L or more, or 300 g / L or more, preferably 470 g / L or less, or 400 g / L or less.

[0198] The solvent in the plating bath is typically water. The pH of the plating bath is preferably 8.0 or higher, or 8.2 or higher, and preferably below 9.0 or 8.8. Ammonia or similar substances can be added to adjust the pH. The temperature of the plating bath is preferably 20°C or higher, or 30°C or higher, and preferably below 60°C or 50°C. The current density during electrolytic treatment is preferably 0.5 A / dm³. 2 Above, or 1A / dm 2 The above is preferably 10A / dm. 2 Below, or 7A / dm 2 the following.

[0199] The plating bath used for electroplating may further contain surfactants.

[0200] After the plating process, it is preferable to clean the structure with a cleaning solution. The cleaning solution is preferably water. The temperature of the cleaning solution is preferably 15°C or higher, more preferably 20°C or higher. In addition, from the viewpoint of reducing damage to the dielectric, it is preferably 70°C or lower, more preferably 60°C or lower.

[0201] After the plating process, it is preferable that the porosity of the metal-containing film formed by the metal patterning process is reduced by 0.9% or more by volume. This results in better adhesion between the metal-containing film formed by laser burning and the plating layer. More preferably, the reduction rate is 1.0% or more by volume, more preferably 1.2% or more by volume, more preferably 1.5% or more by volume, and more preferably 2.0% or more by volume. From the perspective of ease of metal-containing film formation, the reduction rate can be, for example, 60% or less by volume, 55% or less by volume, or 50% or less by volume.

[0202] From the perspective of the efficient interaction between the metal pattern and electromagnetic waves, the thickness of the plating layer (in one embodiment, a copper plating layer) is preferably 1 μm or more and 100 μm or less, more preferably 1 μm or more and 50 μm or less, and even more preferably 2 μm or more and 30 μm or less.

[0203] Example

[0204] The present invention will be further illustrated by the following embodiments, but the present invention is not limited to these embodiments.

[0205] [Evaluation Method]

[0206] [Functional Validation Tests for Metamaterials]

[0207] Using HFSS, a software manufactured by ANSYS, calculations were performed to determine the effect of a 300 GHz electromagnetic wave on a structure. Figure 2 The image shows the reflection direction when incident on the metal pattern region from a 0° angle. The polarization direction of the electromagnetic wave's electric field is perpendicular to the width direction of the metal pattern.

[0208] If electromagnetic waves incident on a structure are reflected in an abnormal direction, the structure is considered to function as a metamaterial.

[0209] (Relative permittivity)

[0210] The relative permittivity of the dielectric was calculated using the TAS7500SL manufactured by Advantest, from the time waveform of the transmitted electric field when a 100 GHz electromagnetic wave passes through the dielectric.

[0211] (Water absorption rate)

[0212] The water absorption rate of the dielectric was determined by dry weight method according to Method A of JIS K7209 using a sample of the same size as the D1 type of ISO 294-3.

[0213] (thickness)

[0214] The thicknesses of the metal layer, dielectric, and metal (copper) pattern (metaatomic atoms) were determined using the following method. After embedding the structure prepared in the examples into epoxy resin, a sample was fabricated by cross-section processing using a FIB apparatus (Ethos NX5000, Hitachi High Technology Co., Ltd.). The thicknesses of each component were determined by measuring the cross-sectional images of the sample taken using an electron microscope (S4800, Hitachi High Technology Co., Ltd.).

[0215] Regarding the thickness of the metal compound layer inside the metaatoms, after the structure was bonded to epoxy resin, the cross-section was processed using a FIB device (product name Ethos NX5000, manufactured by Hitachi High Technology Co., Ltd.) in a manner that allows for cross-sectional analysis using SEM. Then, the magnification was set according to the thickness of the metaatoms within the field of view, and the elemental composition within this range was analyzed using an EDX device (product name S4800, manufactured by Hitachi High Technology Co., Ltd.) at an accelerating voltage of 5kV, and the elemental concentration was calculated.

[0216] (The diameter of the smallest containing sphere of a superatomic atom)

[0217] The diameter of the smallest containing sphere of the metaatomic atom is obtained by taking a microscopic image of a metal (copper) pattern using an optical microscope and then calculating it using image processing in ImageJ.

[0218] [Example 1]

[0219] (Structure Construction)

[0220] A U-imide varnish (manufactured by Unitika) was applied to a copper sphere with a radius of 41.3 mm and cured at 280°C for 1 hour. The cured material (dielectric 12) on the copper sphere was 25 μm thick and had a relative permittivity of 3.0.

[0221] 202 g of copper(II) acetate monohydrate (manufactured by Kanto Chemical Co., Ltd.) was dissolved in a mixed solvent of 1890 g of distilled water (manufactured by Kyoei Pharmaceutical Co., Ltd.) and 874 g of 1,2-propanediol (manufactured by Kanto Chemical Co., Ltd.), and the solution temperature was maintained at -5°C using an external thermostat. 59 g of hydrazine monohydrate (manufactured by Tokyo Chemical Industry Co., Ltd.) was added to the resulting solution over 20 minutes. After stirring for 30 minutes under a nitrogen atmosphere, the solution temperature was maintained at 25°C using an external thermostat, and stirring was continued for 90 minutes. Following stirring, the dispersion was separated into a supernatant and a precipitate by centrifugation.

[0222] A mixture of 13g of DISPERBYK-145 (manufactured by BYK Chemical Co., Ltd.) and 212g of ethanol (manufactured by Fujifilm and Koichi Chemical Co., Ltd.) as a non-volatile organic compound was added to 98g of the obtained precipitate, and the mixture was dispersed using a homogenizer, resulting in 323g of a composition with a cuprous oxide particle concentration of 20% by mass.

[0223] The composition obtained by dip coating on the cured material was dried in an oven at 60°C for 2 hours, and the resulting composition had a thickness of 800 nm.

[0224] For the dried composition, refer to Figure 1Region 11 of the metal (copper) pattern shown in Table 1 was irradiated with a 355 nm laser. The areas where no laser irradiation was applied, leaving dry residue of the composition, were wiped with a non-woven cloth soaked in ethanol.

[0225] like Figure 2 As shown, in region 11 of the metal (copper) pattern, metal (copper) patterns (in one embodiment, metaatoms) 13 are arranged at intervals from #1 to #52 on the surface of the dielectric 12. Additionally, as... Figure 2 As shown, in the cross-sectional plane at the equator of the copper sphere (structure 10), the angle between the straight line connecting the center of the copper sphere and #1 of the metal (copper) pattern 13 and the incident wave is 12.6°.

[0226] like Figure 1 As shown, the metal pattern region 11 is a metal pattern consisting of a rectangular copper layer with a vertical length of 110 μm and a horizontal length of L, arranged in a repeating unit pattern with a vertical period of 150 μm and a horizontal period of 350 μm, forming a metal (copper) pattern 13. The fabrication process is as follows: Figure 1 The structure 10 shown is configured with the metal (copper) pattern 13 and the metal pattern region 11. The smallest enclosing sphere of the metaatoms in the fabricated structure 10 has a diameter of 74.7 μm to 345 μm. The thickness of the metal (copper) pattern 13 is 400 nm.

[0227] It should be noted that Table 1 shows the lateral length L of the metal (copper) pattern 13 (#1 to #52).

[0228] [Table 1-1]

[0229] [Table 1-2]

[0230] For region 11 of the metal (copper) pattern of structure 10, electromagnetic waves with a frequency of 300 GHz were emitted using HFSS manufactured by ANSYS. Figure 2 The calculation shows the reflection direction when incident on the copper pattern area from a 0° direction. The polarization direction of the electromagnetic wave's electric field is perpendicular to the longitudinal direction of the metal (copper) pattern 13. The results are shown in... Figure 3 .

[0231] It should be noted that, Figure 3 The vertical axis represents a value proportional to the electromagnetic wave intensity (unit: none). Figure 3 The horizontal axis represents the angle of the reflection direction (unit: degrees). Figure 3 The horizontal axis will Figure 2 Setting the reflection to the left as negative will affect the direction of reflection. Figure 2 The reflection in the right direction is set to positive.

[0232] Depend on Figure 3 The results confirmed that the incident wave at 0° was as follows: Figure 2 As shown, it reflects abnormally at a 45° angle to the right.

[0233] The structure in Example 1 can control the direction of electromagnetic waves even in directions that cannot be achieved through ordinary mirror reflection and refraction, thus demonstrating its function as a metamaterial.

[0234] [Example 2]

[0235] (Preparation of compositions containing metal compounds)

[0236] 202 g of copper(II) acetate monohydrate (manufactured by Kanto Chemical Co., Ltd.) was dissolved in a mixed solvent of 1890 g of distilled water (manufactured by Kyoei Pharmaceutical Co., Ltd.) and 874 g of 1,2-propanediol (manufactured by Kanto Chemical Co., Ltd.), and the solution temperature was maintained at -5°C using an external thermostat. 59 g of hydrazine monohydrate (manufactured by Tokyo Chemical Industry Co., Ltd.) was added to the resulting solution over 20 minutes. After stirring for 30 minutes under a nitrogen atmosphere, the solution temperature was maintained at 25°C using an external thermostat, and stirring was continued for 90 minutes. Following stirring, the dispersion was separated into a supernatant and a precipitate by centrifugation. A mixture of 17g of DISPERBYK-145 (manufactured by BYK Chemical Co., Ltd.), a non-volatile organic compound, and 100g of ethanol (manufactured by Fujifilm and Koichi Pure Chemical Co., Ltd.) was added to 98g of the obtained precipitate, and the mixture was dispersed using a homogenizer to obtain 216g of a composition of a metal-containing compound containing cuprous oxide particles at a mass concentration of 30%.

[0237] (Structure Construction)

[0238] Reference Figure 4 and Figure 5 Structure 10 is fabricated. A composition containing a metal compound is spin-coated onto the spherical side of a plano-convex spherical glass lens LA1257 (Thorlabs Japan Co., Ltd.), which serves as substrate 16. In an IR furnace, the copper oxide is reduced by heating at 320°C for 120 minutes under a nitrogen-hydrogen mixed gas (hydrogen concentration 3.6 vol%) to form a copper layer as metal layer 15.

[0239] Furthermore, a polyimide varnish (manufactured by Unitika Co., Ltd., U-imide varnish CR) is spin-coated onto the copper layer and cured at 300°C for 1 hour in air using a hot plate to form a polyimide layer serving as dielectric 12. The relative permittivity of this polyimide layer is 3.0.

[0240] Next, a composition containing a metal compound is spin-coated onto a polyimide layer at a rotation speed of 1400 rpm using a spin coater to form a coating film. Multiple metal patterns 13 (metaatomic atoms) are formed by irradiating the coating film with a laser (laser intensity: 30 mW). Excess metal compound coating film in the non-laser-irradiated areas is removed by rinsing with pure water, completing the structure 10.

[0241] The thicknesses of the copper layer (metal layer), the polyimide layer (dielectric layer), and the copper superatoms formed on the spherical surface of the glass lens LA1257 are 1 μm, 25 μm, and 0.4 μm, respectively. The diameters of the smallest enclosing spheres of the superatoms in the fabricated structure 10 range from a minimum of 147 μm to a maximum of 348 μm.

[0242] Figure 4 This is a top view of the structure fabricated in Example 2.

[0243] (Simulation as a functional confirmation of metamaterials)

[0244] For the structure fabricated in Example 2, an HFSS manufactured by ANSYS was used to transmit electromagnetic waves at a frequency of 300 GHz. Figure 4 The calculation of the reflection intensity distribution when the electromagnetic wave is incident from the positive z-axis to the negative z-axis, as described in the paper. The polarization direction of the electric field of the electromagnetic wave is parallel to the y-axis. The results are shown in... Figure 6 and Figure 7 .

[0245] Figure 6 It is the distribution of reflection intensity in the xz plane. Figure 7 This represents the distribution of reflection intensity in the yz plane. Figure 6 and Figure 7 The vertical axis represents the value proportional to the electromagnetic wave intensity (unit: none), and the horizontal axis represents the angle of the reflection direction (unit: degrees). Figure 6 The horizontal axis is set to positive for reflections in the positive y-axis direction and negative for reflections in the negative y-axis direction. Figure 7 The horizontal axis is set to positive for reflections in the positive x-axis direction and negative for reflections in the negative x-axis direction.

[0246] Depend on Figure 6 The results confirmed that the reflected wave was reflected in the xz plane at a tilt of 30.5° from the z-axis, by... Figure 7 The results confirmed that the reflected wave was reflected in the yz plane at an angle of 30.5° from the z-axis. If... Figure 8 That determines the azimuth angle θ of the reflection direction r and polar angle r ,but Figure 6 The angle of the horizontal axis is θ r , r Represented as arctan(tan r cosθ r ), Figure 7 The angle of the horizontal axis is expressed as arctan(tan r sinθ r Therefore, the reflected wave is directed (θ). r , r The electromagnetic waves are reflected in the directions of (45°, 40°). The structure in Example 2 can control the direction of electromagnetic waves even in directions that cannot be achieved through ordinary mirror reflection and refraction, thus demonstrating its function as a metamaterial.

[0247] (As a functional verification test for metamaterials)

[0248] The following method was used to measure the electromagnetic waves with a frequency of 300 GHz emitted from the structure fabricated in Example 2. Figure 4 The ability to control the direction when incident from the positive z-axis direction to the negative direction.

[0249] A variable wavelength laser diode (manufactured by Spectra Quest Lab) is connected to a single-row carrier photodiode (manufactured by NTT Electronics) as an oscillator 33 for electromagnetic waves at 300 GHz. A Fermi level controlled barrier diode (manufactured by NTT Electronics) is used as a photodetector 31. Furthermore, the photodetector 31 is mounted on a moving stage 30 (manufactured by Sigma Opto-Electronics), thereby enabling the photodetector 31 to perform scanning.

[0250] Reference Figure 9 The apparatus is configured such that electromagnetic waves 34 (incident waves) are irradiated onto the structure of Example 2 held in the sample holder 32 by the oscillator 33, and the intensity of the reflected waves 35 reflected by the structure of Example 2 is measured by the photodetector 31. As a result, an angular distribution representing the reflection intensity is obtained. Figure 10 .like Figure 10 As shown, the direction θ was observed r =45° r =45° reflection. Thus, it is confirmed that the structure fabricated in Example 2 functions as a metamaterial.

[0251] [Example 3]

[0252] (Compositions containing metal compounds) (Structure Creation)

[0253] For the metal-containing compound compositions and structures prepared in Example 3, instead of Figure 4 And reference Figure 11 The polyimide varnish was cured under a nitrogen atmosphere, otherwise prepared according to the same steps as in Example 2. The relative permittivity of the polyimide layer was 3.2. The diameter of the smallest enclosing sphere of the metaatoms of the prepared structure 10 ranged from a minimum of 147 μm to a maximum of 348 μm.

[0254] (Simulation as a functional confirmation of metamaterials)

[0255] For the structure of Example 3, the reflection intensity distribution was calculated in the same manner as in Example 2. The results are shown below. Figure 12 and Figure 13 .

[0256] Figure 12 It is the distribution of reflection intensity in the xz plane. Figure 13 This represents the distribution of reflection intensity in the yz plane. Figure 12 and Figure 13 The vertical axis represents the value proportional to the electromagnetic wave intensity (unit: none), and the horizontal axis represents the angle of the reflection direction (unit: degrees). Figure 12 The horizontal axis is set to positive for reflections in the positive y-axis direction and negative for reflections in the negative y-axis direction. Figure 13 The horizontal axis is set to positive for reflections in the positive x-axis direction and negative for reflections in the negative x-axis direction.

[0257] Depend on Figure 12 The results confirmed that the reflected wave was reflected in the xz plane at a 45° angle from the z-axis, by Figure 13 The results confirmed that the reflected wave was reflected in the yz plane in a direction tilted 0° from the z-axis.

[0258] Figure 12 The angle of the horizontal axis is θ r , r Represented as arctan(tan r cosθ r ), Figure 13 The angle of the horizontal axis is expressed as arctan(tan r sinθ r Therefore, the reflected wave is directed (θ). r , r The electromagnetic wave direction can be controlled even in directions that cannot be achieved through ordinary mirror reflection and refraction, thus demonstrating its function as a metamaterial.

[0259] (As a functional verification test for metamaterials)

[0260] The electromagnetic wave with a frequency of 300 GHz was measured using the same method as in Example 2. Figure 11 The directional control capability when incident from the positive z-axis direction to the negative z-axis is recorded. As a result, a representation of the reflection intensity distribution is obtained. Figure 14 .like Figure 14 As shown, the direction θ was observed r =-2° r The reflection is around 45°. Therefore, it is confirmed that the structure fabricated in Example 3 functions as a metamaterial.

[0261] [Example 4]

[0262] (Compositions containing metal compounds) (Structure Creation)

[0263] The metal-containing compound compositions and structures prepared in Example 4, in addition to replacing... Figure 11 And reference Figure 15 Apart from this, it was fabricated following the same steps as in Example 3. The smallest containment sphere of the metaatoms in the fabricated structure 10 has a diameter of 147 μm to 348 μm.

[0264] (Simulation as a functional confirmation of metamaterials)

[0265] For the structure of Example 4, the reflection intensity distribution was calculated in the same manner as in Example 2. The results are shown below. Figure 16 and Figure 17 .

[0266] Figure 16 It is the distribution of reflection intensity in the xz plane. Figure 17 This represents the distribution of reflection intensity in the yz plane. Figure 16 and Figure 17 The vertical axis represents the value proportional to the electromagnetic wave intensity (unit: none), and the horizontal axis represents the angle of the reflection direction (unit: degrees). Figure 16 The horizontal axis is set to positive for reflections in the positive y-axis direction and negative for reflections in the negative y-axis direction. Figure 17 The horizontal axis is set to positive for reflections in the positive x-axis direction and negative for reflections in the negative x-axis direction.

[0267] Depend on Figure 16 The results confirmed that the reflected wave was reflected in the xz plane at a tilt of 43.5° from the z-axis, by... Figure 17 The results confirmed that the reflected wave was reflected in the yz plane in a direction tilted 10.5° from the z-axis.

[0268] Figure 16 The angle of the horizontal axis is θ r , r Represented as arctan(tan r cosθ r ), Figure 17 The angle of the horizontal axis is expressed as arctan(tan r sinθ r Therefore, the reflected wave is directed (θ). r , r The electromagnetic wave direction can be controlled even in directions that cannot be achieved through ordinary mirror reflection and refraction, thus demonstrating its function as a metamaterial.

[0269] (As a functional verification test for metamaterials)

[0270] The electromagnetic wave with a frequency of 300 GHz was measured using the same method as in Example 2. Figure 15 The directional control capability when incident from the positive z-axis direction to the negative z-axis is recorded. As a result, a representation of the reflection intensity distribution is obtained. Figure 18 .like Figure 18 As shown, the direction θ was observed r =13° r The reflection is around 47°. This confirms that the structure fabricated in Example 4 functions as a metamaterial.

[0271] [Example 5]

[0272] (Compositions containing metal compounds) (Structure Creation)

[0273] The metal-containing compound compositions and structures prepared in Example 5, in addition to replacing... Figure 11 And reference Figure 19 Apart from this, it was fabricated following the same steps as in Example 3. The smallest containment sphere of the metaatomic atoms in the fabricated structure 10 has a diameter of 147 μm to 348 μm.

[0274] (Simulation as a functional confirmation of metamaterials)

[0275] For the structure of Example 5, the reflection intensity distribution was calculated in the same manner as in Example 2. The results are shown below. Figure 20 and Figure 21 .

[0276] Figure 20 It is the distribution of reflection intensity in the xz plane. Figure 21 This represents the distribution of reflection intensity in the yz plane. Figure 20 and Figure 21The vertical axis represents the value proportional to the electromagnetic wave intensity (unit: none), and the horizontal axis represents the angle of the reflection direction (unit: degrees). Figure 20 The horizontal axis is set to positive for reflections in the positive y-axis direction and negative for reflections in the negative y-axis direction. Figure 21 The horizontal axis is set to positive for reflections in the positive x-axis direction and negative for reflections in the negative x-axis direction.

[0277] Depend on Figure 20 The results confirmed that the reflected wave was reflected in the xz plane in a direction tilted 30° from the z-axis, by Figure 21 The results confirmed that the reflected wave was reflected in the yz plane in a direction tilted 0° from the z-axis.

[0278] Figure 20 The angle of the horizontal axis is θ r , r Represented as arctan(tan r cosθ r ), Figure 21 The angle of the horizontal axis is expressed as arctan(tan r sinθ r Therefore, the reflected wave is directed (θ). r , r The electromagnetic wave direction can be controlled even in directions that cannot be achieved through ordinary mirror reflection and refraction, thus demonstrating its function as a metamaterial.

[0279] (As a functional verification test for metamaterials)

[0280] The electromagnetic wave with a frequency of 300 GHz was measured using the same method as in Example 2. Figure 19 The directional control capability when incident from the positive z-axis direction to the negative z-axis is recorded. As a result, a representation of the reflection intensity distribution is obtained. Figure 22 .like Figure 22 As shown, the direction θ was observed r =-2° r The reflection is around 28°. Therefore, it is confirmed that the structure fabricated in Example 5 functions as a metamaterial.

[0281] [Example 6]

[0282] (Compositions containing metal compounds) (Structure Creation)

[0283] The metal-containing compound compositions and structures prepared in Example 6, in addition to replacing... Figure 11And reference Figure 23 Apart from this, it was fabricated following the same steps as in Example 3. The smallest containment sphere of the metaatoms in the fabricated structure 10 has a diameter of 147 μm to 348 μm.

[0284] (Simulation as a functional confirmation of metamaterials)

[0285] For the structure of Example 6, the reflection intensity distribution was calculated in the same manner as in Example 2. The results are shown below. Figure 24 and Figure 25 .

[0286] Figure 24 It is the distribution of reflection intensity in the xz plane. Figure 25 This represents the distribution of reflection intensity in the yz plane. Figure 24 and Figure 25 The vertical axis represents the value proportional to the electromagnetic wave intensity (unit: none), and the horizontal axis represents the angle of the reflection direction (unit: degrees). Figure 24 The horizontal axis is set to positive for reflections in the positive y-axis direction and negative for reflections in the negative y-axis direction. Figure 25 The horizontal axis is set to positive for reflections in the positive x-axis direction and negative for reflections in the negative x-axis direction.

[0287] Depend on Figure 24 The results confirmed that the reflected wave was reflected in the xz plane in a direction tilted 29° from the z-axis, by Figure 25 The results confirmed that the reflected wave was reflected in the yz plane in a direction tilted 7.5° from the z-axis.

[0288] Figure 24 The angle of the horizontal axis is θ r , r Represented as arctan(tan r cosθ r ), Figure 25 The angle of the horizontal axis is expressed as arctan(tan r sinθ r Therefore, the reflected wave is directed (θ). r , r The electromagnetic wave direction can be controlled even in directions that cannot be achieved through ordinary mirror reflection and refraction, thus demonstrating its function as a metamaterial.

[0289] [Example 7]

[0290] (Compositions containing metal compounds) (Structure Creation)

[0291] The metal-containing compound composition and structure prepared in Example 7 were prepared following the same steps as in Example 5, except that the laser irradiation intensity on the coating film of the metal-containing compound composition was reduced to 25 mW. The thickness of the copper as a metaatom was 0.4 μm. A copper oxide layer as a metal compound layer was formed at the boundary between the metaatom and the dielectric with a thickness of 0.05 μm. The diameter of the smallest enclosing sphere of the metaatom in the prepared structure 10 was a minimum of 147 μm and a maximum of 348 μm.

[0292] (Simulation as a functional confirmation of metamaterials)

[0293] For the structure of Example 7, the reflection intensity distribution was calculated in the same manner as in Example 2. The results are shown below. Figure 26 and Figure 27 .

[0294] Figure 26 It is the distribution of reflection intensity in the xz plane. Figure 27 This represents the distribution of reflection intensity in the yz plane. Figure 26 and Figure 27 The vertical axis represents the value proportional to the electromagnetic wave intensity (unit: none), and the horizontal axis represents the angle of the reflection direction (unit: degrees). Figure 26 The horizontal axis is set to positive for reflections in the positive y-axis direction and negative for reflections in the negative y-axis direction. Figure 27 The horizontal axis is set to positive for reflections in the positive x-axis direction and negative for reflections in the negative x-axis direction.

[0295] Depend on Figure 26 The results confirmed that the reflected wave was reflected in the xz plane in a direction tilted 30° from the z-axis, by Figure 27 The results confirmed that the reflected wave was reflected in the yz plane in a direction tilted 0° from the z-axis.

[0296] Figure 26 The angle of the horizontal axis is θ r , r Represented as arctan(tan r cosθ r ), Figure 27 The angle of the horizontal axis is expressed as arctan(tan r sinθ r Therefore, the reflected wave is directed (θ). r , rThe electromagnetic wave direction is reflected in the (0°, 30°) directions, enabling directional control even in directions impossible to achieve through ordinary specular reflection and refraction. Therefore, it can be seen that it functions as a metamaterial. (Comparison) Figure 26 and Figure 20 The value of the peak's vertical axis ranges from 3.27 × 10⁻⁶. -5 Increased to 3.33 × 10 -5 ,Compare Figure 27 and Figure 21 From 6.63×10 -6 Increased to 6.67×10 -6 This indicates that the reflectivity is improved by the copper oxide layer inside the metaatoms.

[0297] [Example 8]

[0298] (Compositions containing metal compounds) (Structure Creation)

[0299] The metal-containing compound composition and structure prepared in Example 8 were prepared following the same steps as in Example 5, except that the laser irradiation intensity on the coating film of the metal-containing compound composition was reduced to 22 mW. The thickness of the copper as a metaatom was 0.4 μm. A copper oxide layer as a metal compound layer was formed at the boundary between the metaatom and the dielectric with a thickness of 0.075 μm. The diameter of the smallest enclosing sphere of the metaatom in the prepared structure 10 was a minimum of 147 μm and a maximum of 348 μm.

[0300] (Simulation as a functional confirmation of metamaterials)

[0301] For the structure of Example 8, the reflection intensity distribution was calculated in the same manner as in Example 2. The results are shown below. Figure 28 and Figure 29 .

[0302] Figure 28 It is the distribution of reflection intensity in the xz plane. Figure 29 This represents the distribution of reflection intensity in the yz plane. Figure 28 and Figure 29 The vertical axis represents the value proportional to the electromagnetic wave intensity (unit: none), and the horizontal axis represents the angle of the reflection direction (unit: degrees). Figure 28 The horizontal axis is set to positive for reflections in the positive y-axis direction and negative for reflections in the negative y-axis direction. Figure 29 The horizontal axis is set to positive for reflections in the positive x-axis direction and negative for reflections in the negative x-axis direction.

[0303] Depend on Figure 28 The results confirmed that the reflected wave was reflected in the xz plane in a direction tilted 30° from the z-axis, by Figure 29The results confirmed that the reflected wave was reflected in the yz plane in a direction tilted 0° from the z-axis.

[0304] Figure 28 The angle of the horizontal axis is θ r , r Represented as arctan(tan r cosθ r ), Figure 29 The angle of the horizontal axis is expressed as arctan(tan r sinθ r Therefore, the reflected wave is directed (θ). r , r The electromagnetic wave direction can be controlled even in directions that cannot be achieved through ordinary mirror reflection and refraction, thus demonstrating its function as a metamaterial.

[0305] Compare Figure 28 and Figure 20 The value of the peak's vertical axis ranges from 3.27 × 10⁻⁶. -5 Increased to 3.37 × 10 -5 ,Compare Figure 29 and Figure 21 From 6.63×10 -6 Increased to 6.64×10 -6 This indicates that the reflectivity is improved by the copper oxide layer inside the metaatoms.

[0306] [Example 9]

[0307] (Compositions containing metal compounds) (Structure Creation)

[0308] The metal-containing compound composition and structure prepared in Example 9 were prepared following the same steps as in Example 5, except that the spin-coating speed of the metal-containing compound composition was reduced to 1000 rpm and the laser irradiation intensity of the coating film of the metal-containing compound composition was increased to 34 mW. The thickness of the copper as a metaatom was 0.48 μm. A copper oxide layer as a metal compound layer was formed at the interface between the metaatom and the dielectric with a thickness of 0.12 μm. The diameter of the smallest enclosing sphere of the metaatom in the prepared structure 10 was a minimum of 147 μm and a maximum of 348 μm.

[0309] (Simulation as a functional confirmation of metamaterials)

[0310] For the structure of Example 9, the reflection intensity distribution was calculated in the same manner as in Example 2. The results are shown below. Figure 30and Figure 31 .

[0311] Figure 30 It is the distribution of reflection intensity in the xz plane. Figure 31 This represents the distribution of reflection intensity in the yz plane. Figure 30 and Figure 31 The vertical axis represents the value proportional to the electromagnetic wave intensity (unit: none), and the horizontal axis represents the angle of the reflection direction (unit: degrees). Figure 30 The horizontal axis is set to positive for reflections in the positive y-axis direction and negative for reflections in the negative y-axis direction. Figure 31 The horizontal axis is set to positive for reflections in the positive x-axis direction and negative for reflections in the negative x-axis direction.

[0312] Depend on Figure 30 The results confirmed that the reflected wave was reflected in the xz plane in a direction tilted 30° from the z-axis, by Figure 31 The results confirmed that the reflected wave was reflected in the yz plane in a direction tilted 0° from the z-axis.

[0313] Figure 30 The angle of the horizontal axis is θ r , r Represented as arctan(tan r cosθ r ), Figure 31 The angle of the horizontal axis is expressed as arctan(tan r sinθ r Therefore, the reflected wave is directed (θ). r , r The electromagnetic wave direction can be controlled even in directions that cannot be achieved through ordinary mirror reflection and refraction, thus demonstrating its function as a metamaterial.

[0314] Compare Figure 30 and Figure 20 The value of the peak's vertical axis ranges from 3.27 × 10⁻⁶. -5 Increased to 3.37 × 10 -5 ,Compare Figure 31 and Figure 21 From 6.63×10 -6 Increased to 6.76 × 10 -6 This indicates that the reflectivity is improved by the copper oxide layer inside the metaatoms.

[0315] [Example 10]

[0316] (Compositions containing metal compounds) (Structure Creation)

[0317] The metal-containing compound compositions and structures prepared in Example 10, in addition to replacing... Figure 11 And reference Figure 32 Apart from this, it was fabricated following the same steps as in Example 3. The smallest containment sphere of the superatoms in the fabricated structure 10 has a diameter of 43 μm to 95 μm.

[0318] (Simulation as a functional confirmation of metamaterials)

[0319] For the structure fabricated in Example 10, an HFSS manufactured by ANSYS was used to transmit electromagnetic waves with a frequency of 1.05 THz from... Figure 32 The calculation of the reflection intensity distribution when incident from the positive z-axis direction to the negative z-axis, as described in the paper, is presented. Figure 33 and Figure 34 .

[0320] Figure 33 It is the distribution of reflection intensity in the xz plane. Figure 34 This represents the distribution of reflection intensity in the yz plane. Figure 33 and Figure 34 The vertical axis represents the value proportional to the electromagnetic wave intensity (unit: none), and the horizontal axis represents the angle of the reflection direction (unit: degrees). Figure 33 The horizontal axis is set to positive for reflections in the positive y-axis direction and negative for reflections in the negative y-axis direction. Figure 34 The horizontal axis is set to positive for reflections in the positive x-axis direction and negative for reflections in the negative x-axis direction.

[0321] Depend on Figure 33 The results confirmed that the reflected wave was reflected in the xz plane at a tilt of 30.5° from the z-axis, by... Figure 34 The results confirmed that the reflected wave was reflected in the yz plane in a direction tilted 0° from the z-axis.

[0322] Figure 33 The angle of the horizontal axis is θ r , r Represented as arctan(tan r cosθ r ), Figure 34 The angle of the horizontal axis is expressed as arctan(tan r sinθ r Therefore, the reflected wave is directed (θ). r , rThe electromagnetic wave direction can be controlled even in directions that cannot be achieved through ordinary mirror reflection and refraction, thus enabling it to function as a metamaterial.

[0323] [Example 11]

[0324] (Compositions containing metal compounds) (Structure Creation)

[0325] The metal-containing compound compositions and structures prepared in Example 11, in addition to replacing Figure 11 And reference Figure 35 Apart from this, it was fabricated following the same steps as in Example 3. The smallest containment sphere of the metaatoms in the fabricated structure 10 has a minimum diameter of 345 μm and a maximum diameter of 1082 μm.

[0326] (Simulation as a functional confirmation of metamaterials)

[0327] For the structure fabricated in Example 11, an HFSS manufactured by ANSYS was used to transmit electromagnetic waves at a frequency of 100 GHz. Figure 35 The calculation of the reflection intensity distribution when incident from the positive z-axis direction to the negative z-axis, as described in the paper, is presented. Figure 36 and Figure 37 .

[0328] Figure 36 It is the distribution of reflection intensity in the xz plane. Figure 37 This represents the distribution of reflection intensity in the yz plane. Figure 36 and Figure 37 The vertical axis represents the value proportional to the electromagnetic wave intensity (unit: none), and the horizontal axis represents the angle of the reflection direction (unit: degrees). Figure 36 The horizontal axis is set to positive for reflections in the positive y-axis direction and negative for reflections in the negative y-axis direction. Figure 37 The horizontal axis is set to positive for reflections in the positive x-axis direction and negative for reflections in the negative x-axis direction.

[0329] Depend on Figure 36 The results confirmed that the reflected wave was reflected in the xz plane at a tilt of 30.5° from the z-axis, by... Figure 37 The results confirmed that the reflected wave was reflected in the yz plane in a direction tilted 0° from the z-axis.

[0330] Figure 36 The angle of the horizontal axis is θ r , r Represented as arctan(tan r cosθ r ), Figure 37The angle of the horizontal axis is expressed as arctan(tan r sinθ r Therefore, the reflected wave is directed (θ). r , r The electromagnetic wave direction can be controlled even in directions that cannot be achieved through ordinary mirror reflection and refraction, thus enabling it to function as a metamaterial.

[0331] Industrial applicability

[0332] The structure of the present invention has a three-dimensional curved surface, and is therefore particularly suitable for use in electromagnetic wave control elements.

[0333] Explanation of reference numerals in the attached figures

[0334] 10 Structure

[0335] 11 Metal Pattern Area

[0336] 12,17 Dielectric

[0337] 13 Metallic Patterns (Superatoms)

[0338] 15 Metal Layers

[0339] 16 Substrate

[0340] 30 mobile stations

[0341] 31. Light receiver

[0342] 32 Sample rack

[0343] 33 Oscillators

[0344] 34 Electromagnetic waves

[0345] 35 Reflected wave

Claims

1. A structure having a three-dimensional curved surface. It sequentially comprises a metal layer, a dielectric, and a metal pattern area on the surface of the dielectric. The diameter of the smallest enclosing sphere of the metaatoms constituting the metal pattern region is between 3 μm and 100 mm.

2. The structure according to claim 1, wherein, The metaatom also contains a layer of metal compound.

3. The structure according to claim 1 or 2, wherein, The metals constituting the metaatoms include copper.

4. The structure according to claim 2, wherein, The metal constituting the metaatoms and the metal compound layer comprises copper.

5. The structure according to claim 1 or 2, wherein, A resin layer is also provided on the outer side of the metal pattern area.

6. The structure according to claim 1 or 2, wherein, The carbon / metal elemental concentration ratio of the metaatom is above 1.0 and below 6.

0.

7. The structure according to claim 1 or 2, wherein, The water absorption rate of the dielectric is less than 0.

2.

8. The structure according to claim 1 or 2, wherein, The area of ​​the metal pattern region is 0.09 mm. 2 Above 20m 2 the following.

9. The structure according to claim 1 or 2, wherein, The operating frequency is above 0.3GHz and below 10THz.

10. An electromagnetic wave transceiver system comprising the structure and electromagnetic wave oscillation antenna as described in claim 1 or 2.